PENGARUH EDUKASI FARMASIS TERHADAP MOTIVASI DAN KEPATUHAN PENGGUNA PROGRAM TERAPI RUMATAN METADON DI PUSKESMAS TAMBORA PADA BULAN FEBRUARI - APRIL 2015 - Halim, Marta; Kumala, Shirly; Hersunaryati, Yetti (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2019)
This study was triggered by the large number of users of Methadone Maintenance Therapy Program (MMTP) who Dropped Out due to lack of motivation and compliance. The purpose of this study was to increase the motivation and compliance of the Tambora Community Health Center MMTP users. The study design used the quasi-experimental method with the pretest-the posttest the group was not comparable. Voluntary research samples amounted to 100 with a distribution of @ 50 for the control group (KK) and @ 50 for the treatment group (KE). Based on the results of data analysis, the following results were obtained: (1) There was an increase in the motivation and compliance variables for the group given education with lectures and leaflets. (3) Pharmacist education (variable knowledge, attitudes and actions) simultaneously can increased the motivation of users with a score of 15.4% (p value 0.00 <0.05) in MMTP at the Tambora Community Health Center. (3) Pharmacist education (variable knowledge, attitudes and actions) simultaneously increases the compliance of service users in MMTP Tambora Community Health Center with a score of 12.7% (p value 0.00 <0.05). The Conclusion pharmacist education can increase motivation and compliance to users of Tambora Community Health Center MMTP services.